UPAYA MENINGKATKAN AKTIVITAS BELAJAR BIOLOGI SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) YANG DIAWALI DENGAN PEMBERIAN TUGAS RUMAH DI KELAS X.3 SMA N 1 PULAU PUNJUNG - Agustin, M. N Agustin, M. N (Inovasi Pendidikan, 2018)
The problem of this research was students’activities in studying biology at X 3 class of SMAN 1 Pulau Punjung seemed low. Therefore, the researcher did this Classroom Action Research. The objective of this research was to find out whether the students’ activities in studying biology could be improved through applying Numbered Head Together model, which was started by giving home task. The participants of this research were the students of X 3grade in SMA N Pulau Punjung. This research consisted of two cycles that consisting four meetings. Before doing the research, the researcher has done survey for pra observation data. The students did not have good activities in studying biology, although the teacher has motivated them. At the research, the researcher used Numbered Head Together model, which was started by giving home task and the result showed that the students paid attention to be active in studying biology, however there were not many students who were active. In the last cycle, the researcher gave more attention to this group. As the results, all of the students were success to be active in studying biology.Keyword: Students’ activity, Learning Cooperative Numbered Head Together model